2014
DOI: 10.1080/10496475.2014.932881
|View full text |Cite
|
Sign up to set email alerts
|

Acute and 28-Day Repeated Dose Oral Toxicity ofBauhinia variegata(Caesalpiniaceae) Stem Bark Extract

Abstract: Toxicity of aqueous extract (AE) of stem bark of Bauhinia variegata was evaluated. In the acute toxicity study, Sprague-Dawley rats were treated orally with AE (2,000 or 5,000 mg.kg −1 b.w). The animal behavior and mortality were observed periodically for up to 14 d. In the repeated dose toxicity study, the AE was administered daily at doses of 1,000 or 2,000 mg.kg −1 b.w, for 28 d. Behavior and mortality of animals were observed during the test period and hematological, biochemical parameters and histopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The present result demonstrated that all used BV extract doses (10, 100, 1000, 1600, 2900, and 5000 mg extract/kg body weight) didn't induce any mortality cases in male rats. Moreover, no changes, in general appearance, occurred during the observation period indicating that BV was well-tolerated (orally) in rats up to 5000 mg/kg body weight, this came in agreement with Makadiya et al [29] . An injection of MIA into a rodent's knee joint is a widely used experimental model to study OA [30] .…”
Section: Discussionsupporting
confidence: 90%
“…The present result demonstrated that all used BV extract doses (10, 100, 1000, 1600, 2900, and 5000 mg extract/kg body weight) didn't induce any mortality cases in male rats. Moreover, no changes, in general appearance, occurred during the observation period indicating that BV was well-tolerated (orally) in rats up to 5000 mg/kg body weight, this came in agreement with Makadiya et al [29] . An injection of MIA into a rodent's knee joint is a widely used experimental model to study OA [30] .…”
Section: Discussionsupporting
confidence: 90%
“…Biochemical parameters like plasma total protein, creatinine, albumin, bilirubin, BUN, ALT, AST, ALP, TG, TC, uric acid levels were estimated by using biochemistry analyzer (Erba Chem 7, Germany). [35,36] Plasma samples were also estimated for potassium, sodium, and chloride levels.…”
Section: In Vivo Toxicity Studies Of Paeonolmentioning
confidence: 99%